Sergius of Reshaina, Commentary on Aristotle's ›Categories‹ : Critical Edition and Translation - Arzhanov, Yury (2024)
Sergius of Reshaina (d. 536) is a major figure in the history of the Syriac reception of Aristotle's logic. He studied philosophy and medicine in the late 5th century in Alexandria with the famous Ammonius Hermeiou, whose lectures formed the basis for Sergius' main philosophical work, his extensive Commentary on the Categories. In this treatise, Sergius adapted for his Christian audience the Alexandrian educational model and exegesis of Aristotle logical writings and in this way influenced subsequent centuries of Aristotelian studies in Syriac. The commentary contains an extensive introductory part which deals with the traditional set of preliminaries (prolegomena), e.g., the general division of sciences, the scope of Aristotle's logic in general and of his treatise Categories in particular, etc. Moreover, it includes excurses in natural philosophy and contains extensive "ations from Aristotle's Physics. Thus, Sergius' treatise not only introduced the tradition of exegesis of Aristotle to the Syriac world, but provided Syriac readers with a general introduction to philosophy and logic and thus paved the way for the transmission of Greek sciences and philosophy from Alexandria to Baghdad.